The Effect Of Working Discipline on Employee Performance in PT Perusahaan Gas Negara Tbk Bekasi Area - Nyoman Suardhita; Ahmad Rafik; Irwin Sukrisno Sugeng (Journal of Research in Business, Economics, and Education, 2020)
Human Resources (HR) is a unity of energy and an important element that is very influential for the Agency / Company. For the achievement of a goal, it requires human resources that have discipline in order to create a good performance, so that it will accelerate the achievement of optimal goals. The research method used was observation, documentation, questionnaires, and interviews, using a sample technique with a total of 40 respondents. Calculations for analyzing data using SPSS Version 25 Based on the results of the calculation of the Correlation Coefficient Test obtained a result of 0.805 means it has a strong relationship between work discipline and employee performance. Determination Coefficient Test Results produce R Square value of 0.648 or 64.8% means that 64.8% is influenced by work discipline. In the regression equation yields Y = 11.218 + 0.740X. meaning that if the value of X = 0 or without discipline then the employee's performance is 11.218. If X increases by 1 point or every increase in work discipline by 1, it will increase employee performance by 0.740, which means there is a positive influence between work discipline and employee performance.